P1.023 Molecular Typing of Treponema Pallidum from an Ongoing Syphilis Outbreak in Denmark. (13th July 2013) - Salado-Rasmussen, K; Katzenstein, T L; Gerstoft, J; Cowan, S; Hoffmann, S; Jensen, J S
Abstract : Background: Since 1999, the number of persons diagnosed with syphilis has increased dramatically in Denmark. Molecular typing was used to investigate the epidemiology of Treponema pallidum aiming to understand the dynamics of the epidemic. In recent years the tp0548 gene sequence has been used to further differentiate the subtypes obtained using the CDC typing system (number of 60-base pair repeats within the arp gene and restriction fragment length polymorphism analysis of tpr subfamily II genes) into sequence types. Methods: T. pallidum PCR positive ulcer samples from 219 patients diagnosed in Denmark between 2009 and 2013 were identified for the study. At present, 16 specimens have been analysed and included in the study. Molecular typing was performed by sequence analysis of a 400-base pair region of tp0548 and will be supplemented with the CDC typing system. Clinical data were obtained from the Danish National Syphilis Reporting System where patients diagnosed with early syphilis in Denmark are registered. Results: Sequence analysis of tp0548 revealed three sequence types designated f, g, and c, among the 16 patients. Four patients had tp0548 sequence type f. These patients were all men, and comprised both heterosexual men and MSM. One of the patients was originally from Iran. Eleven patients, including one female, had tp0548 sequence type g. These patients all reported Denmark as country of origin and the majority were habitants of Copenhagen. One patient had tp0548 sequence type c. This patient was a heterosexual man originally from Pakistan. Conclusion: These preliminary results show that a minimum of three tp0548 sequence types are prevalent in Denmark. To further differentiate between strain types, the clinical samples will be characterised using the CDC typing system. This study only included patients with lesions which limit our results to patients with early syphilis.